2003
DOI: 10.1002/jsfa.1568
|View full text |Cite
|
Sign up to set email alerts
|

Meat production using four terminal pig lines

Abstract: The influence of terminal sire (Duroc (D1 and D2), Large White/Pietrain (LW/P) and Large White (LW)) on several meat production and meat quality traits was investigated in 452 male and female offspring of Landrace/Large White dams. Age at slaughter, carcass length, carcass weight and dressing yield were similar for all lines, as was the production of shoulders, chops, and ribs with bacon. D2-sired pigs produced more noble pieces as a percentage of their carcass weight than the other three lines. LW/Pand LW-sir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…A common theme between studies evaluated, however, is that there are conflicting results as to the overall benefit the use of the Duroc breed provides. Some studies have shown a decrease in carcass backfat thickness through the use of Duroc sires (Ramirez and Cava, 2007;Rauw et al, 2003) while others have shown no difference between the Duroc and other breeds such as a Pietran X Large White cross , however this does not show a negative with the use of the breed it just does not show any improvement.…”
Section: Breed Line Selection and Pork Qualitymentioning
confidence: 98%
See 3 more Smart Citations
“…A common theme between studies evaluated, however, is that there are conflicting results as to the overall benefit the use of the Duroc breed provides. Some studies have shown a decrease in carcass backfat thickness through the use of Duroc sires (Ramirez and Cava, 2007;Rauw et al, 2003) while others have shown no difference between the Duroc and other breeds such as a Pietran X Large White cross , however this does not show a negative with the use of the breed it just does not show any improvement.…”
Section: Breed Line Selection and Pork Qualitymentioning
confidence: 98%
“…The Duroc breed is commonly used in selection programs as a terminal sire in crossbred market hog production systems because of its advantages over other breeds in terms of growth rate and meat quality . Because of these reasons, many studies have investigated the possible advantages in using the Duroc breed when compared to other breed lines on traits important for meat quality and carcass composition Ramirez and Cava, 2007;Rauw et al, 2003). A common theme between studies evaluated, however, is that there are conflicting results as to the overall benefit the use of the Duroc breed provides.…”
Section: Breed Line Selection and Pork Qualitymentioning
confidence: 99%
See 2 more Smart Citations
“…Significant differences in results between these methods are also observed due to various procedures used (FILHO et al, 2017). It is also common to classify pork into quality classes (PSE -pale, soft, exudative; RFN -red, firm, nonexudative; DFD -dark, firm, dry and AM -acid meat) on the basis of several criteria measured up to 24 hours after slaughter but both selection of these criteria and their threshold values differ amongst most countries (KAUFFMAN et al, 1993;RAUW et al, 2003;KOĆWIN-PODSIADŁA et al, 2006;FAUCITANO et al, 2010;POSPIECH et al, 2011;PRZYBYLSKI et al, 2012;TARCZYŃSKI et al, 2018;KIM et al, 2016). Therefore, the frequency distribution of pork quality classes could vary which was recently confirmed by CAZADEY et al (2016).…”
Section: Introductionmentioning
confidence: 99%